SISTEM PENDIDIKAN PONDOK PESANTREN - Ahmad Manshur; Hamam Burhanuddin; SITI HIDAYAH (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2021)
This paper aims to explain the education system in Pesantren, the Islamic boarding school education system experienced a shift from the Salafi system to the kholaf system. The problem that arises is the loss of the essence of the basic values ​​education system in Islamic boarding schools when faced with modernity and the development of the times, the education system used indicated reducing, this research is an attempt to make a contribution of thought to Islamic boarding schools in carrying out their educational functions. Especially in developing the basic values ​​of education, input for pesantren in organizing their education system, and funding the construction of the education system in the modern era. The findings of this study are; 1) education system of Islamic Boarding Schools are based on the Qur'an and Al-Hadith, 2) the beginning of its establishment, Islamic Boarding Schools use a traditional education system which in the implementation of teaching uses the sorogan and wetonan systems, implemented the classical system and is currently organizing skill institutions and formal schools, 3). In applying the education system, Islamic boarding schools experience lags in the learning system, this is more because pesantren are less able to accommodate the development of the times and are even indifferent to new findings.